Tetraciclinas e glicilciclinas: uma visão geral Tetracyclines and glycylcyclines: an overview - Elene Cristina Pereira-Maia; Priscila Pereira Silva; Wagner Batista de Almeida; Hélio Ferreira dos Santos; Bruna Luana Marcial; Reinaldo Ruggiero; Wendell Guerra (Química Nova, 2010)
Tetracyclines exhibits activity to a broad range of Gram-negative and Gram-positive bacteria and this fact allied to the low toxicity, low cost, and the advantage of administration by oral route led to their indiscriminate use, which caused the appearance of bacterial resistance to these agents, wich has restricted its clinical utility, though new applications have emerged. On the other hand, the glycylcyclines, semi-synthetic products are similar to tetracyclines, which are active against many bacteria resistant to tetracycline and other classes of antibiotics. The purpose of this paper is to give an overview of this important class of antibiotics focusing on its coordination chemistry and possible applications.